The Role of Nerves in Skeletal Development, Adaptation, and Aging - Tomlinson, Ryan E.; Christiansen, Blaine A.; Giannone, Adrienne A.; Genetos, Damian C. (Frontiers in Endocrinology, 2020)
The skeleton is well innervated, but only recently have the functions of this complex network started to become known. Although our knowledge of skeletal sensory and sympathetic innervation, including the location and subtypes of nerves in bone, is incomplete, we are now able to reconcile early studies utilizing denervation models with recent work dissecting the molecular signaling between bone and nerve. In total, sensory innervation functions in bone much as it does elsewhere in the body – to sense and respond to mechanical stimuli. Similarly, sympathetic nerves regulate autonomic functions related to bone, including homeostatic remodeling and vascular tone. However, more study is required to translate our current knowledge of bone-nerve crosstalk to novel therapeutic strategies to combat skeletal diseases and disorders of low bone mass, including aging.